Blended Learning: Interests, Responsibilities, and Students' Metacognitive Abilities Using the Discovery Model - Fuldiaratman Fuldiaratman*; Issaura Sherly Pamela; Dewi Mariana Elisabeth (Universitas Syiah Kuala, 2023)
Metacognitive activities in the learning process will help students gain lasting memories and understanding. Students should be directed to achieve high competence through various innovative learning activities, one of which is by applying the discovery learning model. This study aims to describe the interests, learning responsibilities and metacognitive abilities of students through the discovery learning model based on blended learning. This study uses a mixed qualitative-quantitative approach with an embedded research design. The sample in this study were 50 students of class XI MIA at SMA Negeri 4 Jambi City who were selected using a purposive sampling technique. The data collection instruments used were learning interest and learning responsibility questionnaires, students' metacognitive ability tests, and interview sheets. The data will be analyzed qualitatively using miles and hubarman and quantitatively using descriptive statistics and inferential statistics. The inferential statistics performed consist of assumption tests (normality test, homogeneity test, and linearity test) and hypothesis testing (T test and correlation test). The results of this study indicate that there are significant differences between learning interest, learning responsibility, and metacognitive abilities of students in class XI MIA 1 and class XI MIA 2, with a significance value of 0.012 for student learning interest, then 0.010 for student learning responsibility, and 0.007 for students' metacognitive abilities. In addition, it is known that there is a significant relationship between the variables of student interest and the metacognitive abilities of class XI MIA students at SMA Negeri 4 Jambi City, which is equal to 0.000